The devil's in the details: Measuring mass violence - Huff-Corzine, Lin (Criminology & public policy, 2020)
Research Mass violence refers to victimization, resulting in multiple deaths and/or injuries. Thus, the measurement of mass violence cannot rest on a single definition or dataset. The purpose of this paper is to decompose mass violence into its various sub-types, discuss measurement issues related to the sub-types, evaluate potential datasets for future studies, and offer practical policy implications. Policy Implication Imposing a standard definition for mass violence at this time would be counterproductive and may stifle research and associated policy implications. We recommend developing an enhanced dataset on mass violence based on the National Incident-Based Reporting System (NIBRS). The advantages of NIBRS include its linkages of fatalities and injuries from the same incident, no limitation on the number killed or wounded, and more information than alternative data sources, maintenance of the current crime data flow from local communities through the state and to the FBI for compilation.